1982
DOI: 10.1007/bf01059183
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiologically based pharmacokinetics of hexobarbital, phenobarbital, and thiopental in the rat

Abstract: A physiologically based pharmacokinetic model, which is an extension of the Bischoff-Dedrick multiorgan model, was developed to described the kinetics of barbiturates (hexobarbital, phenobarbital, and thiopental) in the rat. The model is composed of 11 organ or tissue compartments. The brain compartment was featured as a nonflow-limited organ for some low lipid soluble barbiturates. Michaelis-Menten constants for drug metabolism (Km, Vmax) were determined from in vitro experiments using liver microsomes. Bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 20 publications
0
30
1
2
Order By: Relevance
“…Chiba et al (1990) used the binding of imipramine and desipramine to rat liver microsomes (fu mic ϭ 0.453 and 0.409, respectively) to successfully predict steady-state plasma concentrations. Igari et al (1982) reported similar bindings for hexobarbital and thiopental to microsomes (fu mic ϭ 0.82 and 0.99, respectively) as found currently with similar lipophilic homologs, n-pentyl and n-hexyl barbituric acids (fu mic ϭ 0.95 to 0.73). The effect of physicochemical parameters on microsomal binding from equilibrium dialysis (fu inc ) was demonstrated by Austin et al (2002), resulting in an empirical relationship with LogP/D that predicted the microsomal binding of the barbiturates from this study with fu mic /fu inc ratios between 0.9 and 2.2.…”
Section: Discussionmentioning
confidence: 53%
“…Chiba et al (1990) used the binding of imipramine and desipramine to rat liver microsomes (fu mic ϭ 0.453 and 0.409, respectively) to successfully predict steady-state plasma concentrations. Igari et al (1982) reported similar bindings for hexobarbital and thiopental to microsomes (fu mic ϭ 0.82 and 0.99, respectively) as found currently with similar lipophilic homologs, n-pentyl and n-hexyl barbituric acids (fu mic ϭ 0.95 to 0.73). The effect of physicochemical parameters on microsomal binding from equilibrium dialysis (fu inc ) was demonstrated by Austin et al (2002), resulting in an empirical relationship with LogP/D that predicted the microsomal binding of the barbiturates from this study with fu mic /fu inc ratios between 0.9 and 2.2.…”
Section: Discussionmentioning
confidence: 53%
“…Experimental data and simulations have appeared which invalidate these assumptions (32,33). Furthermore, the effective protein fraction was shown to vary with drug concentration in some of the protein media examined (33). In the present study, mingling of data from different species was minimal.…”
Section: Discussionmentioning
confidence: 75%
“…Particularly strong are arguments against extrapolation of binding data from one species or from one protein concentration to another with the inherent assumptions that binding is independent of these factors. Experimental data and simulations have appeared which invalidate these assumptions (32,33). Furthermore, the effective protein fraction was shown to vary with drug concentration in some of the protein media examined (33).…”
Section: Discussionmentioning
confidence: 93%
“…Table 1, 1, 2, 3, 4,9, 10, 11, 12, 13, 14, 15 summarizes all processes and input parameters relevant for the PBPK models of the six test compounds. A more detailed description of the test compounds and the respective PBPK models can be found in the Supplementary Section SI .…”
Section: Methodsmentioning
confidence: 99%